Fire acupuncture for anti-LGI1 antibody autoimmune encephalitis: a case report - Liu, Yu; Gong, Yu; Wu, Xiao-li; Hao, Xiao-min; Liu, Ji-peng; Li, Yin-yin; Yang, Ke-zhen; Gao, Xin-yu; Zhang, Jing; Zhang, Lin; Zhang, Xu-dong; Wang, Jun; et al. (Frontiers in Neuroscience, 2023)
Autoimmune encephalitis, a class of encephalitis, is clinically characterized by multifocal or diffuse brain injury, including aberrant mental behavior, convulsions, and near-event memory impairment. In this article, we describe a female patient with autoimmune encephalitis who tested positive for leucine-rich glioma inactivated 1 (LGI1) antibodies and had hippocampal inflammatory edema in the lesion area. During the first 3 months of her illness, the patient primarily experienced memory loss, the onset of rigid twitching in her extremities that lasted for 1 min while in remission, and incontinence. After gamma globulin administration, methylprednisolone shock, and other symptomatic therapies during hospitalization, the patient’s psychiatric symptoms and seizures improved considerably; however, she did not fully recover her memory. After receiving fire acupuncture for 6 months, the patient’s understanding, orientation, and calculation skills improved considerably. Her memory and mental state were also improved at the follow-up visit. In this case, the use of fire acupuncture for the treatment of autoimmune encephalitis resulted in favorable outcomes with important benefits for conditions affecting the central nervous system; however, more convincing data are required to support the effectiveness of this treatment method.